PENINGKATAN MINAT DAN HASIL BELAJAR PKN MELALUI PEMBELAJARAN KONTEKSTUAL DENGAN TEKNIK LEARNING COMMUNITY PADA SISWA KELAS V DI SD NEGERI BABADAN SEMESTER 2 TAHUN PELAJARAN 2015/2016 - Taukhid, Hasan (Universitas Muria Kudus, 2016)
This research was motivated by the learning and interest of students of class V to followthe teaching Civics is still lacking. This is evidenced only 7 students from 21 students who meetKKM (65). The subject of this research is class student of SDN Babadan VA 2015/2016 school yearsome 21 people. Results of research on (a) Interests studied before action is taken by 38%,increasing to 85% in cycle 1, and by 90% in cycle 2. That means there is an increased influencesignificantly by 52%. (B) Results prasiklus study gained an average of 54.75%, increased to78.40% in cycle 1, and 84.17% in cycle 2. That means there is an increased influence significantlyby 29.42%. Furthermore, to complete learn at prasiklus obtained figures by 47% increasing to81% the first cycle and 100% duty cycle II. This means there is an increased influence significantlyby 53%. The conclusion that contextual learning with Community Learning techniques canincrease interest and learning outcomes of Civic Education.